Electronic band structure of 1D π-d hybridized narrow-gap metal-organic polymers - Frezza, Federico; Schiller, Frederik; Cahlík, Aleš; Ortega, Jose Enrique; Barth, Johannes V; Arnau, Andres; Blanco-Rey, María; Jelínek, Pavel; Corso, Martina; Piquero-Zulaica, Ignacio (Nanoscale, 2023)
One-dimensional (1D) metal-organic (MO) nanowires are captivating from fundamental and technological perspectives due to their distinctive magnetic and electronic properties. The solvent-free synthesis of such nanomaterials on catalytic surfaces provides a unique approach for fabricating low-dimensional single-layer materials with atomic precision and low amount of defects. A detailed understanding of the electronic structure of MO polymers such as band gap and dispersive bands is critical for their prospective implementation into nanodevices such as spin sensors or field-effect transistors. Here, we have performed the on-surface reaction of quinoidal ligands with single cobalt atoms (Co-QDI) on a vicinal Au(788) surface in ultra-high vacuum. This procedure promotes the growth and uniaxial alignment of Co-QDI MO chains along the surface atomic steps, while permitting the mapping of their electronic properties with space-averaging angle-resolved photoemission spectroscopy. In the direction parallel to the principal chain axis, a well-defined 1D band structure with weakly dispersive and dispersive bands is observed, confirming a pronounced electron delocalization. Low-temperature scanning tunneling microscopy/spectroscopy delves into the atomically precise structure of the nanowires and elucidates their narrow bandgap. These findings are supported with GW0 band structure calculations showing that the observed electronic bands emanate from the efficient hybridization of Co(3d) and molecular orbitals. Our work paves the way towards a systematic search of similar 1D π-d hybridized MO chains with tunable electronic and magnetic properties defined by the transition or rare earth metal atom of choice.